The Role Of Mortgage Loans In Financing The Housing Needs Of University Graduates In The Aspect Of Credit Management - Marcin Sitek , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to analyse the financing of housing needs of university graduates with mortgage loans. An analysis of the role of mortgage loans in financing the purchase of a flat was presented based on statistics concerning borrowers, their age and level of education and in the light of the structure of mortgage loans granted in 2016 and 2017. It was demonstrated that with economic recovery, the purchase of a flat continues to be a luxury for well-educated people aged 25-30 or even 35 years. Furthermore, support from governmental programmes fails to meet the expected outcomes in the case of this group of beneficiaries. Thus in the paper the need of change of managing mortgage credits for young people was emphasized.